(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Fiber lasers play an increasingly pivotal role in numerous scientific and industrial domains, spanning from optical communications to medicine. Their utilization across various technological realms continues to surge, prompting the demand for novel physical methods and principles to precisely measure laser pulse parameters during technological investigations. This article provides an overview of contemporary techniques and approaches employed in measuring the parameters of laser pulses generated by fiber laser systems, with a focus on accurately determining pulse frequency and duration. Special attention is paid to the specific measurement of the relationships between frequency, average power, pulse energy and pulse power for a 20W fiber laser source used for laser color marking on stainless steel.